We stand on guard - Vaughan, Brian K. 1976- (Image Comics, Inc., 2017)
One hundred years in the future, a heroic band of Canadian civilians turned freedom fighters defend their homeland from invasion by a technologically superior opponent--the United States of America
Originally published in single magazine form as We stand on guard #1-6
Keywords: Graphic novels -- United States; War -- Comic books, strips, etc; Civil defense -- Canada; Science fiction comic books, strips, etc; Science-Fiction; Krieg; Bürgerwehr; Canada -- Comic books, strips, etc; United States -- Comic books, strips, etc; USA; Kanada; Comic